The spatial distributions of odorant sensitivity and odorant-induced currents in salamander olfactory receptor cells. - Lowe, G (1991)
1. Suction electrode and whole-cell recording were used to record membrane currents from defined regions of solitary olfactory receptor cells from Ambystoma tigrinum. 2. Under whole-cell current clamp, stimulation of cells with odorants activated an inward current in the cilia, an outward current in the soma, and induced a membrane depolarization. Clamping the membrane potential at its resting value of -70 mV increased the inward ciliary current 5- to 10-fold and abolished the outward somatic current. 3. Local odorant stimulation was accomplished by ejecting an odorant solution into a steady flow of Ringer solution. A suction electrode was used to immobilize a cell in the flow and to record the odorant-induced somatic current. The amplitude of the odorant response increased approximately linearly with the length of cilia exposed to the stimulus, but was independent of the length of dendrite exposed to the stimulus, indicating that odorant sensitivity is predominantly localized to the cilia. 4. The latencies of responses recorded under flow did not vary with the region of the cilia which was exposed to the stimulus. Also, the magnitude of the inward ciliary current activated by odorants was equal to that of the whole-cell current recorded under voltage clamp. These observations indicate that the odorant-induced inward current is predominantly localized to the ciliary membrane. 5. Under whole-cell current clamp, local application of a high-K+ solution generated an outward somatic current when applied to the dendrite, but had no effect when applied to the cilia. This indicates that the density of the resting K+ conductance is lower in the ciliary membrane than in the dendritic membrane. 6. The results above are consistent with the hypothesis that all components of the transduction mechanism are uniformly distributed within the cilia, and that the cilia are electrotonically compact, even during an odorant-induced conductance increase.